Sistem Informasi Produktivitas Dengan Metode Nearest Neighbor Bank Sampah Di PT Anugrah Alam Manunggal - Arsya Amira Anwar; Fitroh Akbar Bimantoro; Dionisius Leonardo RSP; Yohanes Anton Nugroho (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
This research is intended to design a waste bank information system through an action research approach. The object in this study is a group of waste banks under the auspices of the Guwosari Training Center, Bantul Regency. The new system built will strengthen ease of use (easy to use). Two things are proposed in this study, namely improvements to the waste bank manual information system that is already running as an initial diagnosis and the transition from the manual recording system to digital recording through computer devices (applications) with centralized data in one database.